Contributory dimensions on cross-cultural work adjustments for professional Malaysian expatriates in construction industry / Hazirah Azami, Halmi Zainol and Nor Eeda Ali - Azami, Hazirah; Zainol, Halmi; Ali, Nor Eeda (2021)
Cross-cultural work adjustments are crucial issues facing among Malaysian professional expatriates abroad. Thedifficulty in adapting to a new environment is one of the issues that lead to the poor performance of these expatriates. The key to successin becoming a professional expatriate is the ability to adapt and perform in a new environment. The focus of this study is to explore the factors on cross-cultural work adjustments to retain professional expatriates in construction industries. Content analysis was used to determine the influencing dimensions for expatriate adjustment. This study reveals that expatriate’s adjustment in socializing with host nationals, interacting and speaking, following custom or culture of the host country among the elements contribute to cross-cultural work adjustments. The dimensions of cross-cultural work adjustments were identified. The recommendation of this study could contribute to the success of organization thus to enhance sustainability and well-being among Malaysian professional expatriates.